2009
DOI: 10.1002/lsm.20872
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in arm and post‐partum abdominal and flank subcutaneous fat deposits and skin laxity using a bipolar radiofrequency, infrared, vacuum and mechanical massage device

Abstract: This study demonstrates with statistical significance, sustainable reduction in circumference and improvement in appearance of arms and abdomen following treatment with Velashape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 26 publications
0
53
0
4
Order By: Relevance
“…A study performed by Brightman et al [19] demonstrated the benefits of the combination of IR, bipolar RF, vacuum, and mechanical massage. Its efficacy and safety when evaluated on upper arms, abdominal and flank circumferences showed significant reduction in circumference and improvement in the appearance of the arms and abdomen.…”
Section: Upper Arm Neck and Jaw Linementioning
confidence: 97%
“…A study performed by Brightman et al [19] demonstrated the benefits of the combination of IR, bipolar RF, vacuum, and mechanical massage. Its efficacy and safety when evaluated on upper arms, abdominal and flank circumferences showed significant reduction in circumference and improvement in the appearance of the arms and abdomen.…”
Section: Upper Arm Neck and Jaw Linementioning
confidence: 97%
“…For the indications of temporary improvement in the appearance of cellulite or circumference reduction, heating must be deeper. Vacuum can be used to assist in folding skin between electrodes and thereby to increase the penetration depth [20,21].…”
Section: Noninvasive Radiofrequencymentioning
confidence: 99%
“…The IR and RF act synergically, promoting heating in the target tissue, collagen remodeling, and improvement of the adipose tissue metabolic rate. The negative pressure vacuum massage improves circulation and also allows the treatment of both the super fi cial and deep dermal layers [ 3 ] . A recent study has showed the effects of this device on the reduction of cellulite severity and body circumference measures in the buttocks [ 17 ] .…”
Section: Lasers and Lights And Combinationsmentioning
confidence: 99%